Suprasellar germ cell tumours: specific problems and the evolution of optimal management with a combined chemoradiotherapy regimen. - Janmohamed, S; Grossman, AB; Metcalfe, K; Lowe, D; Wood, D; Chew, S; Monson, J; Besser, G; Plowman, P (2002)
OBJECTIVE: Suprasellar germ cell tumours are rare, and there are few series of patients outlining the problems in diagnosis and management, and providing clear guidelines for optimal therapy. We have therefore reviewed our own series of 11 such patients who were managed in a joint endocrinology/clinical oncology setting. PATIENTS AND DESIGN: A retrospective case review assessment of all patients seen within a given time. Clinical, biochemical and radiological findings were reviewed, the types of therapy administered noted, and the responses to treatment analysed. RESULTS: In the years 1977-2001, 11 patients with suprasellar (SS) germ cell tumours (GCT) were seen (germinomatous : nongerminomatous = 8 : 3). SSGCT had an approximately equal sex incidence (M : F, 6 : 5), in contrast to pineal tumours, the commonest site of origin of intracranial GCT and which occur predominantly in men. The median age at presentation was 20 years (range 6-49 years) with a median duration of symptoms before diagnosis of 17 months (range 1-35 months). Polyuria was the commonest presenting symptom (10 patients). Diabetes insipidus occurred in all patients, as did partial or complete anterior pituitary failure. Visual failure was present in 55% of cases. Anorexia, weight loss and disturbed thirst sensation were also common. Positron emission tomography scanning was occasionally useful in the evaluation of suprasellar tumours/pituitary stalk lesions deemed too risky to biopsy. A "central nervous system-friendly" chemoradiotherapy regimen comprising vincristine, etoposide and carboplatin and differential daily dose irradiation, usually administered using a partial transmission block technique, produced a 5-year survival of 100% with low morbidity. Treatment did not correct previously abnormal endocrine function although it did improve vision in three of six patients. CONCLUSIONS: We therefore emphasize the use of techniques other than biopsy in the diagnosis of these patients, note the problems in the management of their fluid control, and highlight the favourable response to a combined chemotherapy-radiotherapy protocol.